The Internationalization and Promotional Strategies of Higher Institutional Centre of Excellence of Tropical Wood and Fibre through the Quintuple Helix Conceptual Framework - Khalina Abdan; Norfaryanti Kamaruddin; Ahmad Adlie Shamsuri (Universiti Sains Islam Malaysia, 2024)
E-Prosiding Seminar Pengantarabangsaan Pengajian Tinggi 2022 (SPPT 2022) : “Melonjakkan Aspirasi Pengantarabangsaan Pendidikan Tinggi Yang Mampan”/ Editor: Rezki Perdani Sawai, Anita Ismail, Junaidah Abu Seman, Ahmad Fadly Nurullah Rasedee, Nuradli Ridzwan Shah Mohd Dali 29 September 2022 Anjuran Bersama: Bahagian Education Malaysia dan USIM Alamiyyah